Regular Friday Recitation as a Space for Women and Spirituality: A Qualitative Anthropological Study in Enhancing the Social Role of Mothers in Sukamaju Village - Suci Cahyati; Irhamudin; Nur Laili (Journal of Research in Islamic Education, 2026)
This study aims to analyze the routine Friday recitation as a space for women and spirituality in enhancing the social role of mothers in Sukamaju Village. Recitation in rural communities not only functions as a religious activity, but also becomes an important social space for women in building relationships and social identity. This study uses a qualitative approach with an anthropological perspective through field studies. The research informants were mothers who actively participate in recitation and were selected using a purposive sampling technique. Data were collected through observation, in-depth interviews, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions using triangulation. The results show that recitation strengthens solidarity, increases spiritual awareness, and encourages women's participation and self-confidence in social life. In conclusion, the routine Friday recitation serves as a means of women's empowerment that strengthens the spirituality and social role of mothers in society.